PROSES PENERIMAAN DUKUNGAN SOSIAL ORANGTUA PADA LAKI-LAKI DALAM PERKAWINAN NYENTANA - Puspani, Ni Luh Koman Desi; Herdiyanto, Yohanes Kartika (Jurnal Psikologi Udayana; Edisi Khusus, 2016)
Sacred vows in a marriage generally requires consent from parents. Likewise in Bali on nyentana marriage, which makes the parents of the men sometimes reject and do not approve of her son who wish to nyentana to the woman's family. Psychologically, the role of parents who participated in the affairs of his marriage is a form of social support from parents. This study was conducted to determine how the acceptance of social support from parents in men which is nyentana marriage, and what are the social support received and needed by men in nyentana marriage from his parents. This research is a qualitative research with a case study approach. Collecting data in this research using observation and interviews on the two Balinese men who do the nyentana marriage with category one person divorced and one person who is not divorced. The results of this research indicate that both mens were nyentana both divorced an non-divorced get the same social support from their parents like information support, instrumental support, emotional support, and esteem support. Based on the acceptance of social support from parents, mens who divorced get the esteem support during the courtship process and get a support again when his wife is pregnant because their parents forbid their wedding before. It’s different with mens who are not divorced get te social support from his parents when their having a baby.   Keywords: social support, parents, men, marriage, nyentana